Comparative Study of Plant Diversity in â€œDurga Sagor Eco Parkâ€ and â€œPlanet Parkâ€ Ecosystem in Barisal, Bangladesh - Islam, Md. Tariqul; Siddeqa, Mawya; Hasan, Md. Fuad; Islam, Md. Rashidul (Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2021)
Biodiversity is a common means of ecosystem resiliency; as a diversified community can withstand in a small to medium scale disturbance or can build back better by using its own resources (species). Two adjacent Eco park eg. Durga Sagor Eco Park and Planet Park of Barisal in the district of Barisal, Bangladesh have managed terrestrial ecosystem with a lot of plant diversity. This study focuses on to formulate a diversity index and assessing ecosystem resiliency by using the index of two different ecosystems. For conducting this research visual screening is conducted by the authors, secondary data sources like annual report of Park authority, books, journals etc. have been used respectively. The major findings of this study are that Durga sagor ecosystem has greater biodiversity than Planet Park ecosystem. The Shannon Index and Shimpson Index of Durga sagor and Planet Park is 2.71, 2.62 and 0.14, 0.13 respectively. Evenness of two adjacent ecosystems is 0.80 and 0.77. Finally the results indicate that Durga sagor ecosystem is more resilient than planet park ecosystem as its biodiversity is greater than Planet Park. In case of any natural disturbance (natural disaster) Durga sagor ecosystem will withstand more time than Planet Park ecosystem. How to cite this article: Md Tariqul Islam, Mawya Siddeqa, Md Fuad Hasan et al. Comparative Study of Plant Diversity in â€œDurga Sagor Eco Parkâ€ and â€œPlanet Parkâ€ Ecosystem in Barisal, Bangladesh. J Adv Res Alt Energ Env Eco 2018; 5(3): 1-4.